PENERAPAN MODEL PEMBELAJARAN INKUIRI UNTUK MENINGKATKAN HASIL BELAJAR SISWA PEMULA PADA PELAJARAN TEMATIK - Tsalitsatul Maulidah,; Sukiyanto, (Jurnal Cendekia Media Komunikasi Penelitian dan Pengembangan Pendidikan Islam, 2019)
This study aims to determine the application of inquiry learning models, student learning outcomes in Thematic subjects the objects around us to beginner students in class V. This research is a type of quantitative analysis using designs in the form of one group pretest and posttest. The study population was all fifth-grade elementary school students, amounting to 23 students' data collection techniques using the method of observation and learning outcomes tests. The instrument to measure learning outcomes using pretest and posttest in the form of objective analysis is multiple choice. Data were analyzed using hypothesis testing with the help of the product-moment formula and Paired Sample t-test. The results of this study indicate that learning using inquiry learning models is shown by the average feasibility of aspects with a range of values ​​of 3.50-3.88. And there is an influence of the inquiry learning model on student learning outcomes in Thematic learning the themes of objects around us in class V, as evidenced by the testing of hypotheses obtained r count = 0.806 and r tables = 0.433. While the Paired Sample t-test significance test, showed a correlation before and after the inquiry learning model was applied at 0.806> α (0.05). Based on the values, it can be concluded that the inquiry learning model has a positive influence on student learning outcomes in Thematic learning of the objects around us in the fifth grade of significantly.